The other Europe? Scandinavian intellectuals and the fragility of democracy in the wake of World War II. Issue 4 (November 2019) - Strang, Johan
It is often argued that the Scandinavian post-war period was marked by a democratic optimism that contrasts with the deep concerns for the inherent dangers of popular sovereignty and the thorough moral reconsideration that took place on the European continent in the wake of World War II. This article seeks to balance this view by exploring what Scandinavian intellectuals believed had caused the collapse of democracy in Europe in the 1930s and what they saw as the main threats to democracy in the emerging post-war societies. Focusing on the fears of socialist planning, concerns about the position of individual rights and freedoms in modern societies, and the anxieties concerning the secular total state, the article suggests that the Scandinavian post-war democratic settlement was indeed built around a different set of ideas from those evident in many other places in Europe, but that it was no less informed by recent historical experiences or concerns for the fragility of democracy.